DEPO MEDROKSI PROGESTERON ASETAT (DMPA) INCREASES BODY MASS INDEX OF ACCEPTORS BUT DECREASES THEIR LIBIDO - Wulandari, Dewi Triloka; Januriwasti, Dian Eka (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Depo Medroksi Progesterone Acetate (DMPA) is one method of contraception. Side effects of this method include weight gain and decreased libido. Meanwhile, one of the factors causing decreased libido is weight. Ideally, the couple of fertile age which is used the contaception is free of sexual making intercourse without fearing pragnant, but,unfortunatelly, the usage of contraception of DMPA indeed, makes the woman libido decreases. Aims: This study aims to determine the correlation of weight weight with libido on KB injectors Depo Medroksi Progesterone Acetate (DMPA) Methods: This research is usedin the cross sectional approach. The Population is the acceptor of contraceptive Planning Program on Depo Medroksi Progesteron Acetate (DMPA).Sampling technique used is purposive sampling. The sample size is 29 women people. Weight is measured by the Body Mass Index (BMI) indicator while libido is measured by a Female Sexual Function Index (FSFI) consisting of 22 questions. The statistical test used is Spearman Rank Correlation Results:The result of the research obtained the most weight at the normal level that is 20 people (68,96%). Libido acceptor mostly decreased libido that is 21 people (72,41%) with libido level most at the level of desire phase disturbance that is 10 people (34,5%), from result of statistic test obtained result there is significant correlation between body weight With libido acceptor of Family Planning injecting DMPA with p value 0.002, and patterned positive, it means that the higher weight of acceptor of injecting DMPA hence higher also libido disorder level. A relationship of 0.573 shows the strength of the intermediate relationship. Conclusion: There is a significant correlation between body weight with libido acceptor of injecting Depo Medroksi Progesteron Acetate (DMPA) with p value 0,002. And patterned positive, the working area of Public Health Center at Ujung Pring Bangkalan East Java meaning that the higher the weight of KB contraceptive injectors DMPA the higher the level of libido disturbances. The correlation coefficient of 0.460 shows the correlation strength of body weight with libido in the intermediate relationship.Â